Medical Personnel Preparedness and Response in Flood Disaster Management: A Literature Review - Ambarsari, Waiduri; Syarif, Ahmad (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Flooding is one of the most common natural disasters in Indonesia. Floods can have far-reaching impacts, not only damaging infrastructure and disrupting the economy, but also posing serious health risks to affected communities, such as diarrhea, leptospirosis, respiratory infections, and skin diseases associated with poor sanitation conditions and water pollution due to flooding. In the face of flood disasters, the preparedness and response of medical personnel is a very important element in reducing health impacts. Objective: To evaluate the preparedness and response of medical personnel in flood disaster management by identifying various factors that influence the effectiveness of emergency response. Methods: The method used was a literature review taken from several sources with a limit of 2019-2023. Results and discussion: As health workers and first responders and service providers in disaster emergency response are required to have higher disaster preparedness than other teams. The implementation of disaster preparedness is not only the responsibility of the government, but also involves community participation, especially health workers. The effectiveness of disaster response is highly dependent on good coordination between institutions, including the government, BNPB, non-governmental organizations, and local communities. Conclusion: The preparedness and response of medical personnel is a crucial component in flood disaster management. Medical personnel, especially nurses, have a central role as first responders in providing emergency care, reducing mortality, and preventing the spread of diseases that often emerge post-disaster.